Dressed for war uniform, civilian clothing and trappings, 1914 to 1918 - Edwards, Nina
Men in khaki and grey squatting in the trenches, women at work, gender bending in goggles and overalls over their trousers, a girl at the Paris theatre in pleated, beaded silk, a bangle on her forearm made from copper fuse wire from the Somme. What people wear matters. Copiously illustrated, this book is the story of what people on both sides wore on the front line and on the home front through the seismic years of World War I. Nina Edwards, reveals fresh aspects of the war through the prism of the smallest details of personal dress, of clothes, hair and accessories, both in uniform and civilian wear. She explores how, during a period of extraordinary upheaval and rapid change, a particular preference for a type of razor blade or perfume, say, or the just-so adjustment to the tilt of a hat, offer insights into the individual experience of men, women and children during the course of World War I.